Modelling Impact of Topography Gradient on Signal Path Loss Along the Road Way for 5G - Azhari, Muhammad Nur Imran; Abdul Aziz, Omar; Din, Jafri; Abd Rahman, Tharek (ELEKTRIKA- Journal of Electrical Engineering, 2017)
Prediction of outdoor path loss, PL, model is crucial for the design and planning of fifth generation (5G) wireless communication systems. Different propagation models have been proposed to approximate cellular network’s coverage for diverse surroundings including for along the road way setting. In Malaysia, Road ways are not entirely on flat terrain with several segments of the roads commonly experience topography elevation. This paper presents simulation studies on the impact of topography gradient towards PL for different millimeter wave frequency bands based on available outdoor PL models. Three outdoor PL models were compared, namely close-in (CI) free space reference distance model, floating intercept model (FI), as well as alpha-beta-gamma (ABG) model. Five millimeter frequency bands at 28, 32, 38, 46 and 73 GHz with different gradients and line-of-sight (LOS) scenarios were investigated in the simulation. PL computation using the selected models indicated that topography elevation along roadways may contribute to deviation of no more than 2 dB relative to computation for flat terrain. However, selection of model used may results in different precision in PL modeling.